MANAJEMEN PEMBELAJARAN MATAN KITAB SAFINATUN NAJAH DALAM MENINGKATKAN KETERAMPILAN MEMBACA KITAB KUNING DI ASRAMA MINIKOM PONDOK PESANTREN MAMBAUL ULUM BATA-BATA PANAAN PALENGAAN PAMEKASAN: MANAJEMEN PEMBELAJARAN MATAN KITAB SAFINATUN NAJAH DALAM MENINGKATKAN KETERAMPILAN MEMBACA KITAB KUNING DI ASRAMA MINIKOM PONDOK PESANTREN MAMBAUL ULUM BATA-BATA - MUHYI, - (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
In the MINIKOM dormitory of Pondok Pesantren Mambaul Ulum Bata-Bata Palengaan Pamekasan, kiai and educators of the MINIKOM class dormitory act as motivators, supervisors and teachers who teach religious sciences, MINIKOM dormitory educators are also learning mates as well as playmates of students. Teachers as implementers in accordance with the instructions of kiai are equipped and given teaching supplies such as methods, strategies, readiness and preparation for teaching so that teachers easily interact conducively with students so that learning is carried out easily, effectively, educationally and fun. This research is a qualitative approach, which is a research approach that produces descriptive data in the form of written/oral data. The methods used to collect data include the interview method, observation method, and documentation method. Based on the analysis of the data obtained, it can be concluded that: First, the togetherness of educators with MINIKOM dormitory students for 24 hours/continuously plays an important role in the success of students, because of the following things: (a) the togetherness of educators replaces the position of parents (b) educators can help students' school assignments (c) educators find solutions experienced by students in the world of education. Second, Education carried out in the MINIKOM Dormitory creates a pleasant learning by paying attention to the place of learning, by carrying out indoor and outdoor learning can enjoy the atmosphere that is not menotonus and can breathe fresh air. Third, Applying good, fun, and sustainable learning motivation. Keywords: Learning Management, Kitab Kuning.